Communication during the COVID-19 pandemic: evaluation study on self-perceived competences and views of health care professionals - Schloegl, Mathias; Singler, Katrin; Martinez-Velilla, Nicolas; Jan, Schildmann; Bischoff-Ferrari, Heike A.; Roller-Wirnsberger, Regina Elisabeth; Attier-Zmudka, Jadwiga; Jones, Christopher A.; Miot, Stephanie; Gordon, Adam L. (European Geriatric Medicine, 2021)
Key summary pointsAim The aims of this study were to describe communication experiences while wearing a mask during the COVID-19 pandemic in 2020, to identify possible mask-related barriers to COVID-19-adapted communications and to investigate whether the ABC mnemonic (A: Attend Mindfully; B: Behave Calmly; C: Communicate Clearly) might address these. Findings The majority of the respondents indicated issues related to lack of time during clinical encounters, uncertainty about how to adapt communication, lack of personal protective equipment, lack of communication skills and lack of information about how to adapt their own communication skills. In addition, the participants indicated acknowledging emotions and providing information using clear, specific, unambiguous, and consistent lay language while wearing a mask were among the main communication challenges created during the COVID-19 pandemic. Finally, the study showed significantly improved self-perceived competency regarding key communication after watching the short video presentation. Message Effective communication in medical encounters must utilize on both verbal and nonverbal skills.
CRIS-Team WoS Importer:2021-07-16